Variables associated with ovarian insufficiency in pediatric oncology patients following chemotherapy - Kaydee M. Kaiser; Pooja Rao; Stephanie J. Estes (Elsevier, 2024)
Background: The gonadotoxic effects of chemotherapy are critical concerns in Pediatric Oncology, given most patients survive their cancer. Future fertility is an important concern in this population, supporting the need for additional research on chemotherapy gonadotoxicity. This study's purpose was to identify associations with premature ovarian insufficiency (POI) in pediatric and young adult female cancer survivors with age at cancer diagnosis, cancer type, and cyclophosphamide equivalent dose (CED). Methods: We retrospectively collected data on pediatric patients with cancer treated between 2008 and 2017. Inclusion criteria included female gender, age 0-25 y at the time of cancer diagnosis, prior treatment with chemotherapy, and documented ovarian hormone levels following chemotherapy completion. Results: Two-hundred and forty-five female patients were identified, of whom 57 had documented ovarian hormone levels following chemotherapy. Five patients (9 %) met the criteria for POI. All of the 5 patients were ≥13-years-old at cancer diagnosis and had lymphoma or solid tumor. While there was statistical significance with older age and presene of POI, there was not when comparing tumor type and POI. The 5 patients with POI received a CED between 0 and 28.4 gm/m2 demomstrating against a dose-dependent relationship. Conclusion: Age ≥13 years at cancer diagnosis and a diagnosis of lymphoma/solid malignancy are predictors of POI in children, adolescents, and young adults., A wide range of CED amongst patients with POI suggests the presence of other factors contributing to ovarian dysfunction.